COVID-19 and arterial hypertension: whether normal blood pressure is a sign of a benign course of COVID-19 - O.V. Kuryata; Ye.O. Frolova; O.I. Stadnyk; V.V. Semenov (Medičnì Perspektivi)
SARS-CoV-2 virus, which causes coronavirus disease 2019 (COVID-19), apart from respiratory manifestations, is able to directly affect the cardiovascular system. Therefore, different from general population target values of blood pressure might be beneficial for the patients with COVID-19. The aim of this study was to investigate whether conventional blood pressure control was associated with the severity of COVID-19. From 260 patients that were hospitalised to the unit subdivision of stable patients of COVID-center between March, 2020, and December, 2020, 163 patients with confirmed infection with SARS-CoV-2 virus and hypertension were selected. The patients were distributed by hypertension control: blood pressure <140/90 mmHg (n=94) and blood pressure ≥140/90 mmHg (n=69). Routine instrumental and laboratory investigations were registered and analysed. The patients were diagnosed and treated according to national and European guidelines. The information about the control of blood pressure was taken from the patients’ medical records. The group of patients with controlled hypertension had higher prevalence of females (p=0.03), 10 years higher median of age (p<0.01) and lower frequency of obesity (p=0.04). The patients with controlled hypertension had lower median of pulmonary injury (p=0.04) and lower frequency of SpO2<92% (p=0.02). Glomerular filtration rate <60 ml/min and proteinuria were detected significantly more frequently in the patients with controlled hypertension (p=0.02). In the presented study blood pressure below 140/90 mmHg before the admission to the hospital was associated with a lower degree of pulmonary injury but with the higher frequency of nephropathy signs. Urine test and blood creatinine monitoring might be beneficial for the patients with COVID-19 and hypertension.